CREATION OF A DIGITAL AFRICAN ARCHIVE - Malan, Pierre (My University, 2012)
Sabinet Gateway, a non-profit organization that promotes and supports library and information services in Africa, has been awarded a $1,8 million grant from the Carnegie Corporation New York to create an African Online Journal Archive. This archive, the first of its kind to contain purely African content, will make academic inputs from all over Africa available for research purposes to local and international organisations and academic institutions. The aim is to create for the first time a central full-text repository of retrospective journal content that contains important African research across a number of fields, including the medical, social sciences and environmental arenas. These materials have unique value, providing not only the vital groundwork for further or related research but assisting to preserve the heritage of the African continent. Stretching over four years, this project includes the sourcing of African journal content, the negotiation of publisher agreements, digitization and indexing of the journal content and the creation of a front end that will make the journal content easily accessible to end users online. As a result the project aims for the archive to contain approximately 90 000 articles.
Keywords: CREATION OF A DIGITAL AFRICAN ARCHIVE